Answer:
x = 3/4
y = 5/4
Step-by-step explanation:
Step:
Substitute−x+2 for y in y=3x−1:
y=3x−1
−x+2=3x−1
−x+2+−3x=3x−1+−3x(Add -3x to both sides)
−4x+2=−1
−4x+2+−2=−1+−2 (Add -2 to both sides)
-4x = -3
x=3/4
Step: Substitute x into the original equation
y=-3/4 + 2
y=5/4
Hope this helps!!
Odd no. 3/6 = 1/2
less than 4 3/6 = 1/2
Answer:
Perimeter = (11x + 12)
Step-by-step explanation:
Since, perimeter of a polygon is represented by the sum of measures of all sides,
Perimeter of the given polygon = 3x + (x + 10) + 5x + (2x + 2)
By adding like terms of the expression,
Perimeter of the polygon = (3x + x + 5x + 2x) + (10 + 2)
= (11x + 12)
Therefore, expression for the perimeter is (11x + 12).
Answer:
He simplified the x coefficients incorrectly
Step-by-step explanation: